A Theoretical Framework for Value Creation: A Multidimensional Strategy/Model for Improving Social Economic Performance. (November 2016) - Miller, Leon
Abstract: The tenets shaping Western civilization's notion of managing economic resources and for political economy indicate that there is a dichotomy between the value in exchange and value in use economic value theories (e.g., that the two are incommensurate at the very least as in Aristotle or that there is even a discrepancy between the two as in Adam Smith). However, recent developments in value creation call for a reconceptualization of the value theory—in terms of how it applies to subjective values, organizational behaviour and economic activity. This article argues that although there is much literature announcing a pendulum shift towards value in use, there is a lack of an adequate explanation of how to resolve the long-standing discrepancy in the value theories. In addition, the literature heralding the new value concept is inadequate in explicating it in terms most useful to practitioner—how it can be applied as a theoretical model for improving performance. This article adds to the body of literature heralding the new value concept and its potential for improving organizational and social economic performances by explaining the factors connected with the value creation concept that make it an effective multidimensional strategy for integrating the economic resources of society to create increased benefit for all stakeholders plus by explaining how the value creation concept can be developed into an integrative theoretical business strategy and/or model.